2000
DOI: 10.1073/pnas.97.14.7748
|View full text |Cite
|
Sign up to set email alerts
|

BRG-1 is required for RB-mediated cell cycle arrest

Abstract: The antiproliferative action of the retinoblastoma tumor suppressor protein, RB, is disrupted in the majority of human cancers. Disruption of RB activity occurs through several disparate mechanisms, including viral oncoprotein binding, deregulated RB phosphorylation, and mutation of the RB gene. Here we report disruption of RB-signaling in tumor cells through loss of a critical cooperating factor. We have previously reported that C33A cells fail to undergo cell cycle inhibition in the presence of constitutivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
216
3
5

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(233 citation statements)
references
References 45 publications
9
216
3
5
Order By: Relevance
“…Several reports showed that BRG1 operates through regulation of these key cellular pathways (Strobeck et al, 2000;Lee et al, 2002;Hendricks et al, 2004;Kang et al, 2004). RB expression seemed to remain unaffected by BRG1 silencing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports showed that BRG1 operates through regulation of these key cellular pathways (Strobeck et al, 2000;Lee et al, 2002;Hendricks et al, 2004;Kang et al, 2004). RB expression seemed to remain unaffected by BRG1 silencing.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, our data suggest that BRG1 silencing altered the homeostasis of DNA repair pathway. In fact, the H2AX activation and the upregulation in the expression BRG1, RB and P53 crosstalk Several reports suggested that BRG1 binds to and regulates the retinoblastoma protein and the tumor suppressor protein p53 (Strobeck et al, 2000;Lee et al, 2002;Hendricks et al, 2004;Kang et al, 2004). These are master genes that control cell cycle arrest, differentiation, apoptosis and/or senescence (Felsani et al, 2006;Galderisi et al, 2006;Campisi and d'Adda di Fagagna, 2007;Oberdoerffer and Sinclair, 2007).…”
Section: Genes Involved In Dna Repairmentioning
confidence: 99%
“…Other more distantly related enzymes include human hBrm, Brg1 and the CHD family (CHD1-7). Of note, human hBrm and Brg1 are two candidate tumor suppressor genes that are implicated in repression of E2F target genes and induction of cell differentiation and senescence, through physical and functional interactions with the pRB protein (33,38,56,76,85,104,105,115,124,134,142). Since E2F target genes are incorporated into SAHF and formation of SAHF requires an intact pRB pathway (88,140), hBrm and/or Brg1 might be involved in SAHF assembly, perhaps through deposition of macroH2A.…”
Section: Incorporation Of Other Sahf Componentsmentioning
confidence: 99%
“…The observation that E1A blocks BRG1-mediated growth inhibition strongly suggests that SWI/ SNF activity is required for normal growth regulation by RB family members (Dunaief et al, 1994;Strober et al, 1996), and BRG1 and BRM contain the RB-binding motif LxCxE and bind RB as well as RB family members p107 and p130 (Dunaief et al, 1994;Strober et al, 1996;Dahiya et al, 2000). Constitutively active RB does not induce G1 arrest in cells that lack BRG1 and BRM expression (Strobeck et al, 2000(Strobeck et al, , 2001Zhang et al, 2000;Reisman et al, 2002). However, restoration of BRG1 or BRM expression reconstitutes RB growth inhibition in such cells.…”
mentioning
confidence: 99%